2023
DOI: 10.3390/educsci13020118
|View full text |Cite
|
Sign up to set email alerts
|

Crisis Management, School Leadership in Disruptive Times and the Recovery of Schools in the Post COVID-19 Era: A Systematic Literature Review

Abstract: Contemporary school leadership has always been considered to be one of the most pivotal factors conducive to school effectiveness as well as a driver of change and strategic innovation involving the development of a strong vision, attendant goals and a relevant plan for implementation, monitoring and review. However, the disruption in the provision of educational services caused by the recent COVID-19 pandemic global outbreak revealed deficits in school leadership theory that were largely associated with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 92 publications
(179 reference statements)
0
35
0
Order By: Relevance
“…These findings align with previous studies showing that employees' affective commitment mediates their willingness to embrace organizational changes and engage in creative and innovative behavior (Soumyaja et al ., 2015). High organizational commitment is associated with positive emotions, intrinsic motivation and increased personal creativity, all of which are crucial for implementing innovative pedagogy, exploring new ideas and fostering collaboration among staff in online teaching (Chatzipanagiotou and Katsarou, 2023; Panisoara et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings align with previous studies showing that employees' affective commitment mediates their willingness to embrace organizational changes and engage in creative and innovative behavior (Soumyaja et al ., 2015). High organizational commitment is associated with positive emotions, intrinsic motivation and increased personal creativity, all of which are crucial for implementing innovative pedagogy, exploring new ideas and fostering collaboration among staff in online teaching (Chatzipanagiotou and Katsarou, 2023; Panisoara et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Schools that are characterized be a clear and empathetic communication towards their employees (Harris and Jones, 2020;Pashiardis and Brauckmann-Sajkiewicz, 2022) are likely to foster a positive organizational climate, encourage innovation and promote high productivity (Chatzipanagiotou and Katsarou, 2023;Da'as et al, 2022). Based on this premise, the current study posits the following hypotheses: H1.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Harris and Jones, 2020). In a recent systematic literature review, Chatzipanagiotou and Katsarou (2023) identified three key types of challenge for school leaders that became evident during the pandemic: (1) logistic challenges posed by the lack of infrastructure, resources and efficient planning in schools; (2) academic challenges (e.g. a transition to remote learning, guidance in online teaching practice); and (3) organisational challenges (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Richard Kern's (2024, this issue) text serves as a timely contribution to put into perspective recent developments in the field of technology‐mediated language teaching and learning. It also provides a relevant framework to reflect on both teachers’ and learners’ digital literacy that can be defined as “a range of abilities of a person, such as searching, evaluating, creating, and sharing digital content through digital technology, and represents the person's ability to apply technology critically [emphasis added]” (Pathiranage & Karunaratne, 2023, p. 2).…”
mentioning
confidence: 99%